Using age-structure for a multi-stage optimal control model with random switching time - Stefan Wrzaczek; Michael Kuhn; Ivan Frankovic (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2019)
The paper presents a transformation of a multi-stage optimal control model with random switching time to an age-structured optimal control model. Following the mathematical transformation, the advantages of the present approach, as compared to a standard backward approach, are discussed. They relate in particular to a compact and unified representation of the two stages of the model, the applicability of well-known numerical solution methods, and the illustration of state- and control dynamics. The paper closes with a simple example on a macroeconomic shock, illustrating the workings and advantages of the approach.
Keywords: 330; optimal control theory; age-structured optimal control theory; multistage; random switch; catastrophic disaster